Tapered cladding diameter profile design for high-power tandem-pumped fiber lasers. (17th March 2016) - Huang, Zhihua; Tang, Xuan; Lin, Honghuan; Wang, Jianjun
Abstract: The thermal effect has become the biggest limiting factor regarding the further power scaling of single mode fiber lasers, and it can lead to coating failure and transverse mode instability. A tapered cladding diameter profile design is proposed for the tandem-pumped fiber laser in this work, as it can smooth the temperature profile and reduce the maximum temperature rise within the fiber tremendously. The improvement in performance of the fiber design is verified by analytical and numerical results.